Peningkatan Prestasi dan Pemahaman Belajar IPA Kompetensi Dasar Listrik Statis dalam Kehidupan Sehari-hari dengan Pembelajaran Kontekstual Model Pengajaran Berbasis Masalah pada Siswa Kelas 9G Semester Ganjil tahun pelajaran 2018/2019 - Purwandari, Eny (Universitas Nahdlatul Ulama Pasuruan, 2022)
The purpose of this study is to improve the achievement of grade 9C students in science subjects with the basic material of static electricity in everyday life by developing contextual learning with problem-based teaching models. This research is based on the student's score which is still low related to the material. The research method is using classroom action research with 2 cycles. In each cycle there are 4 stages consisting of planning, action, observation and reflection. The data collected was then analyzed using a quantitative descriptive approach. The results of the study show that the application of contextual learning with problem-based teaching models can improve student achievement in grade 9C in the odd semester of the 2018/2019 school year in science subjects with static electricity basic material in everyday life. In the first cycle 73.33%, the second cycle 80.00% and the third cycle 88.00%.